Can early hyperglycemia affect the morbidity/mortality of very low birth weight premature infants? - Simovic, Aleksandra; Kuc, Admir; Jevtic, Ema; Kocovic, Aleksandar; Markovic, Slavica; Stanojevic, Marina; Jakovcevski, Maja; Jeremic, Dejan (The Turkish Journal of Pediatrics, 2021)
Background. The study aimed to examine the effect of early hyperglycemia on the morbidity/mortality of very low birth weight premature infants. Methods. This retrospective study included all premature infants with gestational age ≤32 gestational weeks, hospitalized at the Department of Intensive Neonatal Care, Clinical Center Kragujevac, during the period 2017-2019. Hyperglycemia was defined as glycemia of ≥12 mmol/l in one measurement, or > 10 mmol/l in two measurements, at repeated intervals of 2-4 hours. Glycemia was determined from capillary blood, using a gas analyzer of Gem Premier 3000, during the first 7 days of life. Continuous intravenous insulin infusion was administered after ineffective glucose restriction at glycemic values of > 14 mmol/l. Results. Patients with normoglycemia (41/72 (56.94%)) and hyperglycemia (31/72 (43.06%)) did not differ in gender, gestational age, mode of delivery and antenatal administration of steroids, while birth weight had a tendency to be lower in the hyperglycemic group (p=0.052). Hyperglycemia was significantly associated with a low APGAR score at the fifth minute (p=0.048), necrotizing enterocolitis (p=0.011), and shorter duration of mechanical ventilation (p=0.006). Hyperglycemia was associated with significantly more frequent fatal outcomes (35.5%) when compared with the normoglycemic group (4.9%). Accordingly, these patients required inotropic (r=0.036) and insulin therapy (r < 0.001) more often. Retinopathy of prematurity, bronchopulmonary dysplasia and sepsis did not correlate with hyperglycemia in our study. Intraventricular hemorrhage of the first degree was more often associated with normoglycemia in premature infants on prolonged mechanical ventilation while more severe intracranial hemorrhage was more common in the hyperglycemic group but did not result in statistical significance due to the small number of patients. Conclusions. Monitoring glucose levels in the blood of very low birth weight premature infants is clinically important because abnormalities in glucose homeostasis can have serious short-term and long-term consequences.